EFFECT OF NITROGEN AND PHOSPHORUS LEVELS AND RATIOS ON YIELD AND NUTRIENT UPTAKE BY GROUNDNUT IN NORTHERN TRANSITION ZONE OF KARNATAKA - L. SHIVA KUMAR; B. M. RADDER; L. H. MALLIGAWAD; V. MANASA (The Bioscan, 2014)
A field experiment was conducted at Main Agricultural Research Station (MARS), Dharwad to know the effect of nitrogen and phosphorus levels and ratios on yield and nutrient uptake by groundnut in northern transition zone of Karnataka. Groundnut cultivar JL 24 was tried during 2012 with eleven ratios of nitrogen (N) and phosphorus (P2O5 ) fertilizers with potassium level as constant (25 kg K2 O ha-1). The yield attributing characteristics, dry pod yield and nutrient uptake were increased due to increasing N/P fertilizer ratios from 0.00 to 1.00. The treatment receiving N/P fertilizer ratio of 0.50 (30 kg N, 60 kg P2 O5 , 25 kg K2 O ha-1) produced significantly higher dry pod yield (3310 kg ha-1), number of filled pods plant-1 (17.47), total number of pods plant-1 (18.80) and 100 kernel weight (38.50 g). Further, the same treatment recorded significantly higher uptake (147.04 kg N, 23.30 kg P2 O5 , 118.48 kg K2 O, 10.93 kg S ha-1) as compared to all other N/P fertilizer ratios. The treatment receiving N/P fertilizer ratio of 0.50 (30 kg N, 60 kg P2 O5 , 25 kg K2 O ha-1) produced higher kernel yield (2441 kg ha-1). However, it was on par with the treatment receiving N/P fertilizer ratio of 0.33 (2344 kg ha-1).